IBD 2009: Emerging Research Frontiers on the Path to a Cure - A Hillary Steinhart; G Tolomiczenko (Canadian Journal of Gastroenterology)
The Crohn’s and Colitis Foundation of Canada (CCFC) hosted a research symposium in April 2009. The current article presents short synopses of the presentations given at that symposium. Invitees included CCFC-funded clinician-scientists and researchers, research administrators and international leaders in inflammatory bowel disease research. Research challenges were outlined while acknowledging advances made in several domains relevant to informing the search for cures. Following the scientific presentations, discussions endorsed current activities of the CCFC and supported the creation of a new pediatric inflammatory bowel disease initiative.